Review of Sharia Economic Law Regarding Prices and Sizes in Buying and Selling Empang Crabs - Dasir, Ayustiawati; Wafiyah, Ummul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
This study aims to find out the practice of buying and selling crabs at different prices and sizes and to review Sharia economic law regarding the practice of buying and selling crabs. This research uses descriptive and qualitative research methods. The author's data collection technique involves conducting observations, interviews, and documentation. The results of the research show that the practice of buying and selling pond crabs in Watu village, Cenrana subdistrict, Bone Regency is carried out by the collector contacting the fisherman, and the collector usually gives the fisherman a down payment so that when the fisherman gets the sea lobster catch, he immediately gives it to the collector. The practice of determining prices and sizes is that before selling to buyers, collectors have sorted and divided the sizes of crab types with predetermined price differences. Meanwhile, collectors get crabs from fishermen with crabs that have not yet been sorted by type and size, while all those involved in the practice of buying and selling crabs do not understand the existence of ministerial regulations governing the size of crabs. Buying and selling crabs according to Sharia economic law is legal because it complies with the provisions of Islamic law. However, in the practice of buying and selling crabs, buyers only feel burdened by the high prices set. Because in buying and selling, both parties must be equally sincere and willing without anyone feeling disadvantaged.